GALL STONES ASSOCIATED ACUTE PANCREATITIS: A REVIEW OF 50 PATIENTS - Tanvir Ahmad; Farhan Javed; Khalid Mehmood; A.G.Rehan (Journal of University Medical & Dental College, 2018)
ABSTRACT: INTRODUCTION: Incidence of Pancreatitis is increasing day by day in our country and gallstone disease is a major cause of this disease. OBJECTIVE: To assess the treatment and outcome of these patients and compare it to other similar studies done at national and international level. MATERIALS AND METHODS: It is a case series conducted in surgical department of Madina Teaching Hospital Faisalabad having acute pancreatitis due to gall stone disease during the period of Jan 2015 to Jun 2016. RESULTS: Out of 50 patients in our study, 32(64%) patients were female. Patient ages were in range of 17 to 67 years, most in the fourth decade (34%). Out of these, 37(74%) patients were having mild attack according to ranson’s criteria, whereas 10(20%) had moderate and 3(6%) patients had severe attack of pancreatitis.4 (8%) patients had CBD stones at presentation. 6(12%) patients underwent laparotomy due to unclear diagnosis and worsening clinical condition. 3(6%) patients expired in our study, two after laparotomy and one patient expired having worsening of pancreatitis after ERCP. CONCLUSION: Gallstones are a major factor in etiology of acute pancreatitis here in Pakistan so symptomatic gallstone surgery should not be delayed unnecessarily. Early diagnosis based on clinical assessment, lab tests and CT scan is very important for appropriate treatment and to avoid undue laparotomies.